2016
DOI: 10.1097/mnh.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular complications in chronic dialysis patients

Abstract: Structured abstract Purpose of review This review article focuses on the most significant cardiovascular complications in dialysis patients (sudden cardiac death, acute coronary syndromes, heart failure, and atrial fibrillation). Recent findings Current and ongoing research aims to quantify the rate and pattern of significant arrhythmia in dialysis patients and to determine the predominant mechanism of sudden cardiac death. Preliminary findings from these studies suggest a high rate of atrial fibrillation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 62 publications
0
24
0
4
Order By: Relevance
“…Our results found a very high risk of death after ESRD diagnosis which corresponded with the study from Chinese ESRD subjects that the risk of death was high as 50% after 5 years follow-up [ 54 ] and could not demonstrate the beneficial effect of RAAS on death after ESRD diagnosis. It was found that sudden cardiac death was the major cause of death among ESRD patients and the underlying mechanism may be cardiac arrthymia which contribute by bradycardia or asystole or ventricular tachycardia [ 55 57 ]. In addition, the post hoc analysis among the CHOICE (Choices for Healthy Outcomes In Caring for ESRD) cohort of 1041 incident dialysis patients reported that sudden cardiac death is common among patients with ESRD and that inflammation and malnutrition significantly increased its occurrence independent of traditional cardiovascular risk factors [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results found a very high risk of death after ESRD diagnosis which corresponded with the study from Chinese ESRD subjects that the risk of death was high as 50% after 5 years follow-up [ 54 ] and could not demonstrate the beneficial effect of RAAS on death after ESRD diagnosis. It was found that sudden cardiac death was the major cause of death among ESRD patients and the underlying mechanism may be cardiac arrthymia which contribute by bradycardia or asystole or ventricular tachycardia [ 55 57 ]. In addition, the post hoc analysis among the CHOICE (Choices for Healthy Outcomes In Caring for ESRD) cohort of 1041 incident dialysis patients reported that sudden cardiac death is common among patients with ESRD and that inflammation and malnutrition significantly increased its occurrence independent of traditional cardiovascular risk factors [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…CKD is known to be associated with cardiac abnormalities, including patients without heart failure [ 2 ]. Cardiovascular complications are the main cause of the end-stage renal disease (ESRD) patients morbidity and mortality [ 3 ]. The risk of cardiovascular diseases (CVD) increases even in the early stages of CKD [ 4 ].…”
Section: Background and Objectivesmentioning
confidence: 99%
“…3 The risk for cardiovascular disease (CVD) morbidity and mortality remains high in all stages of CKD, 4 including in patients with hemodialysis. 5,6 More patients with CKD die of CVD than of the progression of kidney failure. 7 The increase of homocysteine level, referred as hyperhomocysteinemia, is highly prevalent in CKD patients 8 and associated with an increased risk of CVD complications.…”
Section: Introductionmentioning
confidence: 99%